Towards the Therapeutic Use of Thrombospondin 1/CD47 Targeting TAX2 Peptide as an Antithrombotic Agent. Issue 1 (January 2021) - Jeanne, Albin; Sarazin, Thomas; Charlé, Magalie; Kawecki, Charlotte; Kauskot, Alexandre; Hedtke, Tobias; Schmelzer, Christian E.H.; Martiny, Laurent; Maurice, Pascal; Dedieu, Stéphane
Abstract : Objective: TSP-1 (thrombospondin 1) is one of the most expressed proteins in platelet α-granules and plays an important role in the regulation of hemostasis and thrombosis. Interaction of released TSP-1 with CD47 membrane receptor has been shown to regulate major events leading to thrombus formation, such as, platelet adhesion to vascular endothelium, nitric oxide/cGMP (cyclic guanosine monophosphate) signaling, platelet activation as well as aggregation. Therefore, targeting TSP-1:CD47 axis may represent a promising antithrombotic strategy. Approach and Results: A CD47-derived cyclic peptide was engineered, namely TAX2, that targets TSP-1 and selectively prevents TSP-1:CD47 interaction. Here, we demonstrate for the first time that TAX2 peptide strongly decreases platelet aggregation and interaction with collagen under arterial shear conditions. TAX2 also delays time for complete thrombotic occlusion in 2 mouse models of arterial thrombosis following chemical injury, while Thbs1 −/− mice recapitulate TAX2 effects. Importantly, TAX2 administration is not associated with increased bleeding risk or modification of hematologic parameters. Conclusions: Overall, this study sheds light on the major contribution of TSP-1:CD47 interaction in platelet activation and thrombus formation while putting forward TAX2 as an innovative antithrombotic agent with high added-value. Abstract : Supplemental Digital Content is available in the text.